1993
DOI: 10.1523/jneurosci.13-04-01511.1993
|View full text |Cite
|
Sign up to set email alerts
|

Single mossy fiber axonal systems of human dentate granule cells studied in hippocampal slices from patients with temporal lobe epilepsy [published erratum appears in J Neurosci 1993 Jun;13(6):following table of contents]

Abstract: Previous histological and immunocytochemical studies suggest that reorganization of the dentate granule cell axons, the mossy fibers, can occur in epileptic human hippocampus (Sutula et al., 1989; Houser et al., 1990; Babb et al., 1991) and in animal models of epilepsy (Tauck and Nadler, 1985; Sutula et al., 1988; Cronin et al., 1992). However, neuroanatomical analyses of the trajectory and morphology of reorganized axons are not yet available. The present study was conducted to investigate single dentate gran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
0
2

Year Published

1996
1996
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(65 citation statements)
references
References 32 publications
(42 reference statements)
3
60
0
2
Order By: Relevance
“…We found a high coherence of Timm scores 2 and 3 and presence of fluorescent mossy fibers, indicating that the Timm staining provides evidence for aberrant MF sprouting. This is in line with a previous report showing coincidence of intracellularly labeled aberrant mossy fiber arborization and positive staining for zinc or dynorphin in the inner molecular layer (Isokawa et al, 1993). However, the fluorescent-labeled axons in the inner molecular layer may also identify GABAergic or peptidergic axonal systems, involved in reorganization (de Lanerolle et al, 1989(de Lanerolle et al, , 2003Furtinger et al, 2001;Wittner et al, 2001).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found a high coherence of Timm scores 2 and 3 and presence of fluorescent mossy fibers, indicating that the Timm staining provides evidence for aberrant MF sprouting. This is in line with a previous report showing coincidence of intracellularly labeled aberrant mossy fiber arborization and positive staining for zinc or dynorphin in the inner molecular layer (Isokawa et al, 1993). However, the fluorescent-labeled axons in the inner molecular layer may also identify GABAergic or peptidergic axonal systems, involved in reorganization (de Lanerolle et al, 1989(de Lanerolle et al, , 2003Furtinger et al, 2001;Wittner et al, 2001).…”
Section: Discussionsupporting
confidence: 92%
“…Morphological investigation of the resected tissue revealed that one group of TLEs is associated with hippocampal sclerosis (HS) characterized by segmental or total cell loss, whereas another group shows less segmental cell loss (non-HS) (Babb et al, 1984;Kim et al, 1990;Mathern et al, 1997a). In specimens with HS, the axons of granule cells [mossy fibers (MF)] send collaterals into the dentate inner molecular layer (IML) (Scheibel et al, 1974;Sutula et al, 1989;Houser et al, 1990;Masukawa et al, 1992;Isokawa et al, 1993) and form multiple asymmetric synapses with dendritic structures of granule cells (Babb et al, 1991;Franck et al, 1995;Zhang and Houser, 1999). This rearrangement is associated with increased immunoreactivity for glutamate receptors in the IML (Babb et al, 1996;Ying et al, 1998), suggesting that a recurrent excitatory network of granule cells might be present in sclerotic tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Third, N-methyl-D-aspartate and GABA receptor-mediated inputs to CA3 pyramidal cells occur in s. radiatum and oriens, with strong GABA A inhibition associated with somatically localized receptors (42,44,45). Further, in various forms of hippocampal pathology (e.g., mesial temporal sclerosis associated with temporal lobe epilepsy), there is a sprouting of zinc-rich MFs back on to the granule cells of origin (18,20,46,47). Their aberrant terminal localization and their proximity to GABA receptors have prompted investigators to postulate a role for zinc in the breakdown of inhibition that is associated with seizure generation in epileptic hippocampus (48).…”
Section: Morphological Characteristics Of Mf Boutons (Mfbs) Inmentioning
confidence: 99%
“…Dendritic abnormalities are also associated with developmental brain disorders (Purpura et al, 1982;Armstrong, 2005;Dierssen and Ramakers, 2006). This is true in epilepsy where a loss of dendritic branches and spines are commonly observed (Ward, 1969;Belichencko et al, 1992;Isokawa et al, 1993;Multani et al, 1994). Both glutamatergic and GABAergic synaptic transmission have been proposed to play important roles in regulating dendritic growth (Barbin et al, 1993;Rajan and Cline, 1998;Sin et al, 2002;Wayman et al, 2006).…”
Section: Introductionmentioning
confidence: 99%